A Conceptual Framework Explaining the Impact of Perceived Career Growth and Organisational Justice on Intention to Stay Among City Traffic Police Lahore - Adal Mehmood, Sultan; Nadarajah, Devika; Saood Akhtar, Muhammad; Ahmed Brohi, Noor; Ahmed Khuhro, Mansoor (International Journal of Engineering and Technology, 2018)
This paper presents the conceptual framework of intention to stay among City Traffic Police, Lahore.  The high turnover rate among city traffic police officers in Lahore has drawn the attention of the Government as well as academicians. It is believed that city traffic police in Lahore may feel there is limited prospects of career growth and may have negative perceptions on organisational justice. Nevertheless, this has yet to be examined in greater detail. Therefore, this conceptual paper offers a research opportunity to study the impact of perceived organisational justice and career growth on officer’s intention to remain in the organisation. Social exchange theory is applied to this framework. Following this conceptual paper, a full study will be carried out using quantitative research methods. It is hoped that the findings will benefit the City Traffic in Lahore and contribute to the body of knowledge on social exchange theory.